The Phenomenon of Cell Phone Addiction and Its Implications for the Religious Discipline of Students at SMA Negeri 1 Sape - Nur Atika; Muslimin; Kaharuddin (Lembaga Bale Literasi, 2026)
This study aims to examine the phenomenon of cellphone addiction and its implications for the religious discipline of students at SMA Negeri 1 Sape. This research uses a qualitative descriptive approach, with data collected through interviews, observation, and documentation. The results of the study show that cellphone dependence among students at SMA Negeri 1 Sape has a significant impact on discipline in worship. This phenomenon disrupts students' concentration and understanding of the material being presented, because excessive use of cellphones, especially for social media and digital games, distracts them from worship. However, there are several steps that can be taken to address this problem, such as limiting the use of mobile phones in the school environment, stricter supervision by teachers and parents, and providing guidance to students about the importance of wise and balanced mobile phone use.